Soy protein sensitization in cow’s milk allergy patients - Dina Muktiarti; Zakiudin Munasir; Alan R. Tumbelaka (Paediatrica Indonesiana, 2007)
Background The management of cow’s milk allergy (CMA) isavoidance of cow’s milk as strictly as possible. Extensive hydrolyzedprotein and amino acid based formulas are recommended dietaryproducts for treatment of CMA. However, they have somedisadvantages, such as bitter taste and high cost. Alternativeprotein sources from vegetable proteins, such as soy, can be usedas milk-substitute. Previous studies showed the prevalence of soyallergy in CMA patients in Western countries ranged between 0to 63%, but the prevalence in Asia was not greater than 20% andno data about this prevalence in Indonesia.Objectives To determine the proportion of soy proteinsensitization in CMA patients and characteristics of CMA patientswho were sensitized to soy protein.Methods Fifty seven CMA patients who consumed soy proteinwere taken their blood sample to examine the soy-specific IgE.Results From 57 CMA patients, we found only 18% of patientswho were sensitized to soy protein. Seven out of ten CMA patientswho were sensitized to soy protein were under 12 months old.Atopic dermatitis was the most frequent clinical manifestation(8/10) and all of them had family history of atopic diseases. Soysensitization in IgE-mediated and non-IgE mediated CMA were6/10 and 4/10, respectively.Conclusions Proportion of soy sensitization in CMA patients inthis study was 18%. Soy protein can be used as an alternative forcow’s milk substitute in CMA patients.